THE EFFECT OF CARBONATED DRINKS ON ORTHODONTIC STAINLESS STEEL TO HYPERSENSITIVITY TYPE IV - Nabila Alifia Nugroho; Grahita Aditya; Tahta Danifatis Sunnah (Jurnal Medali, 2023)
Background: Orthodontic treatment is a treatment that aims to correct malrelation and malformations to restore masticatory function, esthetics and obtain a good arrangement of teeth to achieve proper occlusion. The bracket is a component in orthodontic treatment that functions as a force conductor. The use of a bracket with a type of stainless steel material has several advantages such as an economical price, corrosion resistance, and high strength, but the habit of consuming carbonated drinks in stainless steel bracket users can cause the release of Ni ions, which can trigger hypersensitivity reactions in some person. Information is needed regarding the relationship between the release of Ni ions on a stainless steel bracket soaked in carbonated drinks to type IV hypersensitivity reactions, especially to an increase in the number of neutrophil cells. Method: The design of this study used a post-test group design using a sample of 10 male Wistar rats which were divided into 2 groups (n = 5), namely the treatment group and the control group. Calculation of the number of neutrophils using histopathological observations with Hematoxylin-Eosin staining using an electric microscope with 400x magnification. Result: The average number of neutrophils in the treatment group was 4.14 and the control group was 1.04. Statistical tests using the Welch T-Test showed significant differences between the two groups (P